On the issue of interdisciplinary aspects of phonosemantic research - E. P. Korchagina (Дискурс)
Introduction. This article is dedicated to the review of foundation and development of phonosemantics, which is known to be quite a young field of linguistics. The background and reasons for the foundation of iconic words research are analyzed, as well as current issues of this field, including the potential of its interaction with other sciences.Materials and Methods. The works of linguists, dediated to this issue, have been used as the research material. They have been analyzed in order to draw out peculiarities and the key phases in the formation of phonosemantics. The aim of the analysis comprises the creation of a general overview of the historical development of phonosemantics. In addition to analysis, another method used in the research implies description.Results. The results of the research work comprise the presentation of phonosemantics foundation and development, its main ideas and research direction. The work also states the perspectives of language iconicity studies as a separate scientific field, as well as in collaboration with other branches of linguistic studies.Discussion. All in all it is worth mentioning that modern phonosemantic research offers a major degree of theoretical studies, which can be considered as a problematic field due to lack of empirical research.Conclusion. It should be underlined that phonosemantics has a great research potential, not only as a general scientific field, but also as a major interdisciplinary research field.